When health is the deadline: Dengue fever, AH1N1 flu and media-epidemic cycles - Waisbord, Silvio (Folios, revista de la Facultad de Comunicaciones y Filología, 2012)
This article takes into account the recent coverage of dengue and the emergence of the AH1N1 virus as a starting point to analyze the factors that contribute to informative “media-epidemic cycles”. The main objective isn’t to provide a detailed analysis of specific media coverage in a country. The intention is to contribute to the analysis of the influence of professional values and routines of journalists in the construction of news on epidemic issues. Such practices pose challenges for the discussion on health areas and public health actions.